Translation and Technical Communication: Chicken or Egg? - Minacori, Patricia; Veisblat, Lucy (Meta, 2010)
Translation starts with a document in one language and ends with a document with the same meaning in another language. Technical communication entails designing and writing a document from scratch in one language. The answer to the question of “Which, of translation or writing, comes first?” seems relatively obvious – the document needs to be written before it can be translated. However, when looking at translation and technical communication as professions and examining how the professionals are trained, the answer is not quite as clear-cut. In the United States, translators and technical communicators have different qualifications, different skills – in particular different language skills – and have degrees in different fields. Only recently has there appeared a certain convergence between the professions. In Europe, and more specifically in France, the profession of technical communicator is quite recent, as are the corresponding academic programs. Many technical communicators came to the profession from translation. The convergence therefore is perceived as being far greater. The purpose of this paper is to launch a comparative study of the competences or skills of translators and technical communicators, based on the existing European Master’s in Translation (EMT) list of competences for translators. The goal of this study would be to define the core skills for technical communicators, to examine to what extent they overlap with the competences of translators and ultimately, to establish a referential for training programs in technical communication.